Active Learning as A Teaching Method: A Discourse for Its Implementation in Islamic Education - Hidayatullah, Syarif (Proceeding International Conference on Religion, Science and Education, 2022)
There are many critiques toward our Islamic education, among them is about incapacity either in developing or braveness to create innovation teaching methods in classroom. It’s caused by our attitude that tends to reduce function of education as a just learning activity. In this context, this paper tries to present a discourse on how we should do penetration in learning process of our classroom. Along with emergence of paradigm alteration of educational system in university from TCL (Teacher Center Learning) to SCL (Student Center Learning) models, so a Active learning method is become a relevant and significance strategy to be implemented in our classroom. The implementation of the Active learning method in Islamic education system will bring into reality our expectation in order to students become moralized persons who own reason wits and heart sharpness in actualizing Islamic values. Because, the Active learning method able to build and develop students character and personality, including to guide their attention toward real problem and requirement. In addition, this method stimulates students to getting critical thinking and problem solving skills; that needed in creating muslim succes in their daily life with society.